Functional segments and software defined trends in enterprise networks - Pratiba Deenadhayalan; Ramakanth Kumar Pattar; Vijay Chiranjith Reddy (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
In the current scenarios most of the business growth comes from the user experience, while using the business applications. Any enterprise network performance depends on the fundamental process of securely serving the user with applications. The network usage patterns have completely changed from just data transfer, voice, and video transmissions to serving entire applications over the networks. With all the modern applications served over the private and public clouds the network resources utilization must be optimized and take full advantage of them which is not possible with current network architectures. The enterprises are currently shifting towards software defined implementation due to many reasons like consistent policy application across the network, run time analytics for troubleshooting the problems and making the network cloud computing ready. Software defined approaches provide centralized security monitoring and control, user data and identity-based segmentation over the network, dynamic recovery from network infrastructure failure and finally virtualization of almost everything. This paper is an overview of the functioning of enterprises in the networking perspective along with current software defined approaches being used in enterprise networking which will soon take over the traditional networks by solving the challenges present in the software defined networking.